1998
DOI: 10.1007/bfb0055883
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of annealing techniques for academic course scheduling

Abstract: Abstract. In this study we have tackled the NP-hard problem of academic class scheduling (or timetabling) at the university level. We have investigated a variety of approaches based on simulated annealing, including mean-field annealing, simulated annealing with three different cooling schedules, and the use of a rule-based preprocessor to provide a good initial solution for annealing. The best results were obtained using simulated annealing with adaptive cooling and reheating as a function of cost, and a rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“…Consequently, T reheat will take a value that is only a very small way above T pt . In both [10] and [51] this method of reheating is reported to be very effective at producing good timetables; indeed, as we will see in our own SA algorithm documented in Chapter 6 later, it is also appropriate for our needs as well. showing how we can use this information to calculate T pt .…”
Section: One Stage Optimisation Algorithmsmentioning
confidence: 89%
See 1 more Smart Citation
“…Consequently, T reheat will take a value that is only a very small way above T pt . In both [10] and [51] this method of reheating is reported to be very effective at producing good timetables; indeed, as we will see in our own SA algorithm documented in Chapter 6 later, it is also appropriate for our needs as well. showing how we can use this information to calculate T pt .…”
Section: One Stage Optimisation Algorithmsmentioning
confidence: 89%
“…Abramson [9], Melicio et al [79], and Elmohamed et al [51] have also reported one-stage optimisation algorithms that make use of the simulated annealing (SA) metaheuristic. In the approach of Elmohamed et al, for example, the authors consider the timetabling problem of Syracuse University in the USA and use a weighted-sum scoring function that heavily penalises violations of the hard constraints.…”
Section: One Stage Optimisation Algorithmsmentioning
confidence: 99%
“…Unfortunately, SA also has many well-documented disadvantages. It requires extensive computational work [1,15,34,53]. Furthermore, SA is sensitive to the choice of its many parameters which can be difficult to fine tune [1,15,38,41,47,53].…”
Section: Simulated Annealingmentioning
confidence: 99%
“…It requires extensive computational work [1,15,34,53]. Furthermore, SA is sensitive to the choice of its many parameters which can be difficult to fine tune [1,15,38,41,47,53]. For example, there are at least a dozen different temperature cooling schedule from which to choose [18,26,44,53].…”
Section: Simulated Annealingmentioning
confidence: 99%
“…Since then, the problem has been tackled with various approaches including graph coloring [23], network flows [6] and operations research methods [1]. During the last years, various artificial intelligence techniques have also been used against the problem, like tabu search [3], [30], simulated annealing [9], [27], genetic algorithms [24], [10] and constraint programming [16], [22], [19], [11], [26].…”
Section: Introductionmentioning
confidence: 99%